Cerebellum and semantic memory: A TMS study using the DRM paradigm. (February 2021) - Gatti, Daniele; Vecchi, Tomaso; Mazzoni, Giuliana
Abstract: Traditionally, the cerebellum has been linked to motor functions, but recent evidence suggest that it is also involved in a wide range of cognitive processes. Given the uniformity of cerebellar cortex microstructure, it has been proposed that the same computational process might underlie cerebellar involvement in both motor and cognitive functions. Within motor functions, the cerebellum it is involved in procedural memory and associative learning. Here, we hypothesized that the cerebellum may participate to semantic memory as well. To test whether the cerebellum is causally involved in semantic memory, we carried out two experiments in which participants performed the Deese-Roediger-McDermott paradigm (DRM) while online transcranial magnetic stimulation (TMS) was administered over the right cerebellum or over a control site. In Experiment 1, cerebellar TMS selectively affected participants' discriminability for critical lures without affecting participants' discriminability for unrelated words and in Experiment 2 we found that the higher was the semantic association between new and studied words, the higher was the memory impairment caused by the TMS. These results indicate that the right cerebellum is causally involved in semantic memory and provide evidence consistent with theories that proposed the existence of a unified cerebellar function within motor and cognitive domains, as well with recent perspectives about cerebellar involvement in semantic memory and predictive functions.